A novel photochemical sensor based on quinoline-functionalized phenazine derivatives for multiple substrate detection. (2nd March 2021) - Wei, Tai-Bao; Dong, Hong-Qiang; Ma, Xiao-Qiang; Yang, Qing-Yu; Wang, Zhong-Hui; Guan, Wen-Li; Zhang, Yun-Fei; Zhang, You-Ming; Yao, Hong; Lin, Qi
Abstract : A novel photochemical sensor based on quinoline-functionalized phenazine derivatives for highly sensitive detection of multiple substrates (l -Arg, CO2, and pH) was designed and synthesized. Abstract : A novel photochemical sensor (FQ-5 ) based on quinoline-functionalized phenazine derivatives was designed and synthesized. The FQ-5 showed a good response to certain pH values in a wide pH range (from 2.0 to 13.0). Particularly, at pH = 12 and 13, the fluorescence emission showed obvious enhancement, the fluorescence quantum yields could reach 80.9% and 77.0%, respectively, and the color of solution changed from yellow to purple. Meanwhile, the sensor not only showed a rapid response toward CO2, but also showed high selectivity and sensitivity for the detection of l -Arg in buffer solution (pH = 7), and the limit of detection (LOD) was 8.1 × 10 −8 . Furthermore, the FQ-5 -based fluorescent writing material and CO2 gas reaction device were developed for the rapid detection of l -Arg and CO2 . Therefore, this work will provide a new approach for photochemical sensing in the detection of multiple substrates.